Over a million students use our free study notes to help them with their homework
(6x-2)/4 - (3x+3)/3 = (1-x)/3multiply both sides of the equation by 12=lowest common multiple of 4 and 33(6x-2) - 4(3x+3) = 4(1-x)expand brackets18x - 6 -12x - 12 = 4 - 4xsimplifyAnswered by Eleanor L. • Maths tutor2604 Views
So far in your learning it is likely that you have been learnt that if you can't factorise a quadratic equation then you can not solve for x. The quadratic formula is overcomes this restriction, allowing ...
Full Explanation:We have our Equation: y=(x+4)2+7At the turning points, the gradient, (m) is zero m=0 = dy = 0To work out the g...
Mean for all students: (the sum of all the heights)/total number of students = (the sum of boys+sum of girls)/30 = 1.6sum of boys and girls = 1.6 x 30Mean for girls: (the sum of all the girls' heights)/to...
(x + 2)2+3
←
641
642
643
644
645
→
Internet Safety
Payment Security
Cyber
Essentials